2010
DOI: 10.1007/s00540-009-0861-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of propofol and ketamine on renal injury in unilateral ureteral obstruction

Abstract: Propofol as an anesthetic agent may attenuate NO-induced renal tubular cell apoptosis by downregulating the expression of iNOS in an animal model of unilateral UO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…More importantly, in rats that underwent PHT under propofol anesthesia, there was less iNOS staining than in those that underwent PHT under ketamine anesthesia. Dikmen et al 34 reported that ketamine does not reduce iNOS-mediated NO production upon renal injury in unilateral ureteral obstruction. Those findings suggest that propofol might limit iNOS overexpression and exhibit an anti-apoptotic profile.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, in rats that underwent PHT under propofol anesthesia, there was less iNOS staining than in those that underwent PHT under ketamine anesthesia. Dikmen et al 34 reported that ketamine does not reduce iNOS-mediated NO production upon renal injury in unilateral ureteral obstruction. Those findings suggest that propofol might limit iNOS overexpression and exhibit an anti-apoptotic profile.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The mechanism underlying the hepatoprotective effect of propofol may be explained by the results of studies demonstrating that propofol can produce non-anesthetic organ-protective effects. The latter include: reduction of the generation and scavenging of free radicals; inhibitory effects on calcium channels and reduction of intracellular calcium overload; reduction of the chemotaxis of inflammatory cells; reduction of NO production and apoptosis by downregulation of iNOS expression 34,38 . The antioxidant activity of propofol may mediate its potential role as a modulator of apoptosis 41 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…31 Based on current evidence, norepinephrine should be used to restore blood pressure within autoregulatory values in hypotensive vasodilated patients with acute kidney injury. 31 According to previous knowledge, propofol is down regulated by nitric oxidase synthase to preserve renal function 32 and protect renal tissue via peroxidation of lipid membrane. 33 Lee et al reported that propofol reduced the new onset of chronic kidney disease after nephrectomy.…”
Section: Original Article Smjmentioning
confidence: 99%
“…It is a highly lipid-soluble anesthetic that has antioxidant activity against lipid peroxidation under in vitro and in vivo conditions [6]. It inhibits renal renal injury through down-regulating inducible nitric oxide synthase expression [7] and protects HK-2 human kidney proximal tubular epithelial cells against stress induced by H2O2 [8]. Other synthetic opioid analgesic is Fentanyl that is an opioid agonist.…”
Section: Introductionmentioning
confidence: 99%